(untitled) (Research, Society and Development, 2021)
Objective: Evaluate menu satisfaction and compare the acceptability of vegetarian preparations between vegetarians and omnivores. Methodology: Cross-sectional study carried out in two UR in Vitória-ES (campus 1 and 2). Data collection occurred through the application of a questionnaire to identify the acceptability of vegetarian dishes, in addition to measuring rest-intake. The data were analyzed in SPSS, adopting p <0.05. Results: 19.2% of the participants were vegetarians, who had a median age similar to omnivores (22 years old). The majority were female (53.9% of omnivores and 68.2% of vegetarians), which was associated with vegetarianism (p<0.001). Vegetarian Kibbeh was the only dish that showed a difference in acceptability scores, the largest being atributed by omnivores. The least acceptable preparation was the Soy Pie. Menu satisfaction was low on both campuses, given high levels of rest-intake. Conclusion: Information on the satisfaction of the menu and the profile of the customers of food and nutrition units are important in satisfying public service and in promoting good environmental practices.